Determinants of Diversification from Oil Sector in Saudi Arabia - Alkhathlan, Khalid Abdullah; Alkhateeb, Tarek Tawfik Yousef; Mahmood, Haider; Bindabel, Wardah Abdulrahman (International Journal of Energy Economics and Policy, 2020)
Saudi Arabia targets diversification policy in the Vision 2030. This study estimates the production, exports, government revenue, investment and employment diversification indices and also finds its determinants. Increasing inflation promotes the production and export diversification and depresses the investment, government revenue and employment diversification. The depreciation policy encourages the government revenue diversification and reduces investment and employment diversification. Foreign Direct Investment (FDI) improved the government revenue diversification and weakens the export diversification. Economic growth stimulates the government revenue, employment and export diversification and slow down the production and investment diversification. Government spending improves the production and investment diversification and dampens the government revenue and exports diversification. Capital formation promotes the export diversification and reduces the government revenue and employment diversification. Money supply diminishes the investment, government revenue, exports and employment diversification. Subsidies expand production diversification and contract the government revenue diversification. Trade openness lifts up the investment and employment diversification and reduces the government revenue diversification. Keywords: diversification, exports, government revenue and spending, money supply JEL Classifications: L25, B17, E62, E52 DOI: https://doi.org/10.32479/ijeep.9709